Sosialisasi Penyuluhan Pentingnya Imunisasi di Kampung Kadu Pereup - Irma Ainni; Hudefah Hudefah; Rahma Virly Aulia Milova; Zafira Az Zahra; Kurniati Rahmadani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
This community service work program aims to make people aware of the importance of the benefits of immunization for pregnant women and toddlers, to prevent various diseases. Health is an important foundation in life, through immunization children will have a good immune system, and will not get sick easily. Various diseases that can be prevented through immunization include tuberculosis, measles, tetanus and other diseases that are transmitted through viruses. This outreach discusses the importance of immunization and at the same time invites the public to diligently attend the routine posyandu that the local government has organized. This activity was carried out with posyandu activities for approximately 3 hours, held in Kadu Pereup Village, Kubang Baros Village, Cinangka District, Serang Regency.